Variation in Utilization of Health Care Services for Rural VA Enrollees With Mental Health‐Related Diagnoses. Issue 3 (19th January 2015) - Johnson, Christopher E.; Bush, Ruth L.; Harman, Jeffrey; Bolin, Jane; Evans Hudnall, Gina; Nguyen, Ann M.
Abstract Purpose Rural‐dwelling Department of Veterans Affairs (VA) enrollees are at high risk for a wide variety of mental health‐related disorders. The objective of this study is to examine the variation in the types of mental and nonmental health services received by rural VA enrollees who have a mental health‐related diagnosis. Methods The Andersen and Aday behavioral model of health services use and the Agency for Healthcare Research and Quality Medical Expenditure Panel Survey (MEPS) data were used to examine how VA enrollees with mental health‐related diagnoses accessed places of care from 1999 to 2009. Population survey weights were applied to the MEPS data, and logit regression was conducted to model how predisposing, enabling, and need factors influence rural veteran health services use (measured by visits to different places of care). Analyses were performed on the subpopulations: rural VA, rural non‐VA, urban VA, and urban non‐VA enrollees. Findings For all types of care, both rural and urban VA enrollees received care from inpatient, outpatient, office‐based, and emergency room settings at higher odds than urban non‐VA enrollees. Rural VA enrollees also received all types of care from inpatient, office‐based, and emergency room settings at higher odds than urban VA enrollees. Rural VA enrollees had higher odds of a mental health visit of any kind compared to urban VA and non‐VA enrollees. Conclusions Based on these variations, the VA may want to develop strategies to increase screening efforts in inpatient settings and emergency rooms to further capture rural VA enrollees who have undiagnosed mental health conditions.